2018
DOI: 10.1177/2158244018807320
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Management, Knowledge Creation, and Open Innovation in Icelandic SMEs

Abstract: The aim of this article is to present findings on knowledge management (KM) and knowledge creation, as well as open innovation in small and medium-sized enterprises (SMEs) in Iceland. Two SME company case studies are presented in the form of a case study involving semistructured interviews with managers and selected employees and in-field observation. Company Alpha is a software company, whereas Company Beta is a family company which produces drinks and snacks. Knowledge creation and innovation is a learning p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
2
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 61 publications
6
56
2
6
Order By: Relevance
“…Thus, the hypothesis 1a should be rejected as it cannot be asserted that there is difference in drivers for open innovation between high-tech and non-high-tech industries. These results are opposite to those of Hagedoorn [1993], Schmidt [2007], Oduro [2019] as well as Grimsdottir and Edvardsson [2018], who found that driver for open innovation differ significantly across industries, but it supports the study of Chesbrough and Crowther [2006] who founded out no difference in drivers for open innovation between high-tech and non-high-tech industries. Primary driver leading to the adoption of open innovation is a search for growth opportunities.…”
Section: Resultscontrasting
confidence: 63%
See 2 more Smart Citations
“…Thus, the hypothesis 1a should be rejected as it cannot be asserted that there is difference in drivers for open innovation between high-tech and non-high-tech industries. These results are opposite to those of Hagedoorn [1993], Schmidt [2007], Oduro [2019] as well as Grimsdottir and Edvardsson [2018], who found that driver for open innovation differ significantly across industries, but it supports the study of Chesbrough and Crowther [2006] who founded out no difference in drivers for open innovation between high-tech and non-high-tech industries. Primary driver leading to the adoption of open innovation is a search for growth opportunities.…”
Section: Resultscontrasting
confidence: 63%
“…Commercialization motive along with knowledge acquisition, financial and strategic motives were also found to be significant for SMEs of low-tech industries in Ghana [Oduro, 2019]. Different practices are observed between two businesses in open innovation, one in software products (high-tech industry) and the other in agribusiness (non-high-tech industry) according to Grimsdottir and Edvardsson [2018]. The literature on open innovation also indicates that a knowledge-poor environment, which is a characteristic of non-high-tech industries does not motivate, but can inhibit the adoption of open innovation [van de Vrande et al, 2009;Garriga et al, 2013;Verbano et al, 2015].…”
Section: Drivers and Barriers For Open Innovation In Different Industmentioning
confidence: 91%
See 1 more Smart Citation
“…The relationship with customers is crucial for the growth of competitiveness of SMEs. Grimsdottir and Edvardsson (2018) report that communicating of SMEs with customers is extremely important as a source of new knowledge. Customer demand for new products and services and the willingness of employees and managers of SMEs to meet these requests play a major role in this process.…”
Section: Theoretical Partmentioning
confidence: 99%
“…Therefore, output or the final products of the knowledge created is not only organizational practices but managerial systems and new methods that characterize the knowledge about customers through knowing and exploring their needs and attitudes (Hislop et al, 2018). According to Grimsdottir and Edvardsson (2018) the initial starting point of knowledge management is Knowledge creation. Massaro et al (2016) adds that Knowledge creation has a crucial impact on in developing and enhancing innovation.…”
Section: Introductionmentioning
confidence: 99%